Germination Behaviour and Storability of Ailanthus excelsa Seeds - Rawat, M. M. S.; Naithani, K. C.; Thapliyal, R. C. (Indian Forester)
The seeds of Ailanthus excelsa exhibited orthodox storage behaviour as viability period increased with the decrease in storage temperature and seed moisture content. Seeds dried to 5.7% moisture content remained viable, with 50% of the initial germination, beyond three years at 5Â°C and beyond one year at ambient room temperature. The seeds are non-dormant and germinate freely at 30Â°C on top of paper, the conditions found ideal for testing germination capacity.